ANALISIS KESULITAN MENULIS CERITA NARASI BERDASARKAN GAMBAR TUNGGAL PADA SISWA KELAS II SD NEGERI 2 KIARAJANGKUNG KECAMATAN SUKAHENING - Mida Azzahro Qurbati, Dudung Suryana, Riga Zahara Nurani (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2025)
One of the problems in learning Indonesian is the difficulty of students in expressing their thoughts to write narrative stories. The difficulties faced by students such as difficulties in imagining, developing their ideas, understanding images, composing stories. Based on these problems, this study aims to analyze the obstacles experienced by students in writing narrative stories based on single images, to describe the forms of difficulties faced by students and to describe internal and external factors. The research methodology uses descriptive qualitative research. Data collection techniques used are observation, tests, interviews and documentation. The results of the study showed that the forms of difficulties in writing narrative stories based on single images are difficulties in imagining, difficulties in developing ideas in the form of stories and difficulties in composing stories. Internal factors of the difficulty in writing narrative stories based on images are the way of holding and moving the pencil so that this makes it difficult for students to write stories. External factors that influence the difficulty of writing narrative stories based on single images in class 2 of SDN 2 Kiarajangkung are students who cannot pay attention to the teacher's explanation and the lack of motivation and guidance from their family environment.